2018
DOI: 10.15414/jmbfs.2018.7.6.555-561
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF DRIED FAECAL SLUDGE AND MUNICIPAL WASTE CO-COMPOST ON MICROBIAL LOAD AND YIELD OF CABBAGE (Brassica oleracea L. var. capitata) AND LETTUCE (Lactuca sativa)

Abstract: Municipal waste management has been of major concern to many developing countries and is presently one of the subjects under discussion due to rapid industrialization and population growth. Most of these municipal wastes have the potential of being recycled and use in crop production. They are gradually becoming a problem in Ghana instead of being used for purposes to benefit human kind. In this study, dried faecal sludge and municipal waste co-compost was used as an organic fertilizer to cultivate cabbage and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Yet, measurements taken on days 29 th and 35 th showed the biofertilizers were significantly lower than the chemical treatment. A previous study observed the most significant changes in the lettuce height happened between the 3 rd and the 5 th week of cultivation when fertilized with sludge cocomposted with organic waste (TORGBO et al, 2018), which was the period the chemical fertilizer stood out from the other treatments in the present study.…”
Section: ) Pradhan Et Al (2010) Applied Urine For Beetroot Cultivatio...mentioning
confidence: 49%
See 1 more Smart Citation
“…Yet, measurements taken on days 29 th and 35 th showed the biofertilizers were significantly lower than the chemical treatment. A previous study observed the most significant changes in the lettuce height happened between the 3 rd and the 5 th week of cultivation when fertilized with sludge cocomposted with organic waste (TORGBO et al, 2018), which was the period the chemical fertilizer stood out from the other treatments in the present study.…”
Section: ) Pradhan Et Al (2010) Applied Urine For Beetroot Cultivatio...mentioning
confidence: 49%
“…For Torgbo et al (2018), the use of co-compost from fecal sludge and municipal waste presented higher plant height than chemical fertilizers. Applying struvite supplemented with KCl in maize production led to a similar result in plant height, with no significant difference from chemical fertilizer (LIU et al…”
Section: Resultsmentioning
confidence: 99%
“…Oleh karena itu, kondisi tanah perlu diperbaiki dengan pemberian pupuk organik. Limbah pertanian dapat dijadikan sebagai bahan dasar bahan organik yang bertujuan untuk meningkatkan kesehatan tanah disamping untuk mengatasi limbah yang semakin melimpah (Yano dan Sakai, 2016;Matsuda, et al, 2017;Torgbo, et al, 2018). Pemberian bahan organik pada tanah dapat meningkatkan suatu daya produksi tanah karena bahan organik tersebut dapat memperbaiki sifat fisik, kimia maupun biologi tanah (Susanti, 2015;Danial, et al, 2020).…”
Section: Pendahuluanunclassified
“…and Klebsiella spp. (mean value of microbial loads = 1.18 × 10 7 CFU per ml) on harvested vegetables than even chemical fertilizers (2.45 × 10 9 CFU per ml) or the control plot with no treatment (5.2 × 10 8 CFU per ml) (Torgbo et al, 2018). Soobhany (2018) observed that composting organic municipal solid waste led to significant reduction in total coliforms (from 3.13–3.57 to 1.52–2.89 log 10 most probable number [MPN] per gram) and E .…”
Section: Introductionmentioning
confidence: 99%
“…While reduction in pathogens is essential, it is also important that the beneficial impacts of the organic wastes are retained. In Ghana, Torgbo et al (2018) observed a significant increase in the yield of vegetables cultivated on agricultural soils amended with the recommended rates of N as compost. The head weight of cabbages grown with compost was significantly higher (53.3 g) than those grown with inorganic fertilizer (32.9 g) and the control with no treatment (31.4 g).…”
Section: Introductionmentioning
confidence: 99%